(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
Contrary to the commonly held notion that Sufis are generally apolitical, contemporary scholars on Sufism, in general, have reached a consensus that Sufism has always been tinged with political colour. However, this perspective, though dominant, seems to under-appreciate the nuances of Sufism and at the same time denies Sufis’ capacity to remain non-partisan whenever they choose to be. Against this backdrop, this article attempts to investigate four Sufi-regimes that have been politically active in contemporary Bangladesh. Analysing their evolution, it explains the stage in their growth when such regimes are likely to remain non-partisan and when they are likely to shed their visibly apolitical stance, take noticeably more political positions and/or form political party. It argues that before taking on an explicitly political character, a typical Sufi-regime usually undergoes at least three identifiable phases – namely, recognition, expansion and stabilisation, and lastly discipline through organisation. According to the analytical model presented here, Sufis in the recognition and expansion phase are unlikely to join politics, while those with a disciplined group of followers and murids can participate in the political process with a minimum level of encouragement from their respective surroundings. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 1-32